The Influence of Financial Literacy and Risk Perception on Investment Decisions (Survey of Management Students at the University of Perjuangan Tasikmalaya 2025) - Muhammad Andi Fadhilah; Ghaling Achmad Abdul Ghonisyah; Kusuma Agdhi Rahwana (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to determine the influence of financial literacy and risk perception on investment decisions, both simultaneously and partially. The research method used to examine the influence of financial literacy and risk perception on investment decisions is a quantitative method with a descriptive and survey approach. The sample in this study consisted of 92 students from the Management Study Program at the University of Perjuangan Tasikmalaya. The data used were primary data. The analytical tool employed in this study was multiple regression analysis using SPSS version 26.0. The results of the study show that the level of financial literacy among students of the Management Study Program at the University of Perjuangan Tasikmalaya falls into the “very good” category. Similarly, their risk perception and investment decision-making are also categorized as “very good.” Simultaneously, financial literacy and risk perception have a significant influence on investment decisions. Partially, financial literacy has a significant effect on investment decisions, and risk perception also has a positive and significant influence on investment decisions.